2020
DOI: 10.1039/d0ce00856g
|View full text |Cite
|
Sign up to set email alerts
|

Selective polymorphism of α-glycine by acoustic levitation

Abstract: This work demonstrates the selective crystallisation of α-glycine from water and a binary solvent mixture by acoustic levitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Glycine was used as reference molecule, being widely used in crystallization studies. [23][24][25] A droplet (2 mL) of water or glycine solution was drop cast onto the patterned electrode area, as shown schematically in Fig. 1B.…”
Section: Resultsmentioning
confidence: 99%
“…Glycine was used as reference molecule, being widely used in crystallization studies. [23][24][25] A droplet (2 mL) of water or glycine solution was drop cast onto the patterned electrode area, as shown schematically in Fig. 1B.…”
Section: Resultsmentioning
confidence: 99%
“…31 In contrast to previous works, we exploit the fact the Raman spectroscopy is extremely sensitive to the molecular packing, including small structural alterations such as bond lengths, dihedral angles, and hydrogen bonding patterns. 33 In particular, it has been shown that the positions of the two CH stretching vibrations not only allow for the identification of the glycine polymorph, 34 but can also be used to identify the dihedral angle ξ, defined by atoms N-C-C-Ocis to N, Figure 1a, hence providing direct information on the molecular arrangement. By fitting the CH stretching peaks and determining how their splitting difference changes during the evaporation of the solvent, we observed that there is a sharp transition in the molecular arrangement from solvated molecules to glycine crystals, with the final polymorph being α-glycine (ξ ~ 18), in agreement with previous results.…”
Section: Introductionmentioning
confidence: 99%
“…31 In contrast to previous works, we exploit the fact the Raman spectroscopy is extremely sensitive to the molecular packing, including small structural alterations such as bond lengths, dihedral angles, and hydrogen bonding patterns. 33 In particular, it has been shown that the positions of the two CH stretching vibrations not only allow for the identification of the glycine polymorph, 34 but can also be used to identify the dihedral angle ξ , defined by atoms N–C–C–O cis to N, Fig. 1a, hence providing direct information on the molecular arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…This is the simplest amino acid, which has wide applications in the pesticide, pharmaceutical, food, feed additive, and daily chemical industries, and thus, sufficient experimental data on its crystallization behavior are available. Glycine has three polymorphs, of which the γ-form is the thermodynamically most stable, the α-form is metastable, and the β-form is extremely unstable and easily transforms to the α- and γ-forms . Despite thermodynamic considerations, crystallization from aqueous solutions under ambient conditions typically yields the metastable α-form, as it is kinetically favored. , Therefore, α-glycine crystal growth under ambient conditions is studied in this work. It is well known that additives often impact the crystallization behavior of the primary solute, influencing crystal habit (shape) and even form (polymorphism), which, in turn, can affect both downstream processing and product formulation .…”
Section: Introductionmentioning
confidence: 99%
“…24 Despite thermodynamic considerations, crystallization from aqueous solutions under ambient conditions typically yields the metastable α-form, as it is kinetically favored. 29,30 Therefore, α-glycine crystal growth under ambient conditions is studied in this work. It is well known that additives often impact the crystallization behavior of the primary solute, influencing crystal habit (shape) and even form (polymorphism), which, in turn, can affect both downstream processing and product formulation.…”
Section: ■ Introductionmentioning
confidence: 99%